Austronesian undressed how and why languages become isolating - Gil, David; Schapper, Antoinette (Typological studies in language,, 2020)
"Many Austronesian languages exhibit isolating word structure. This volume offers a series of investigations into these languages, which are found in an "isolating crescent" extending from Mainland Southeast Asia through the Indonesian archipelago and into western New Guinea. Some of the languages examined in this volume include Cham, Minangkabau, colloquial Malay/Indonesian and Javanese, Lio, Alorese, and Tetun Dili. The main purpose of this volume is to address the general question of how and why languages become isolating, by examination of a number of competing hypotheses. While some view morphological loss as a natural process, others argue that the development of isolating word structure is typically driven by language contact through various mechanisms such as creolization, metatypy, and Sprachbund effects. This volume should be of interest not only to Austronesianists and historians of Insular Southeast Asia, but also to grammarians, typologists, historical linguists, creolists, and specialists in language contact"--